Review of Legal Policy Concerning Payment of Book Royalties in Indonesia Based on Copyright Law - Dahris Siregar (Faculty of Law, Universitas Pekalongan, 2022)
This study aims to find out how the study of legal policy regarding payment of book royalties in Indonesia is based on the Copyright Act, the royalty payment system must of course be through an agreement between the two parties, namely between the publisher and the author of the manuscript. The agreement is made after the manuscript is received and deserves to be published by signing the SPPB (Book Publishing Agreement). The royalty amount for the purchase system is decided by mutual agreement between the publisher and the author. Publishers give royalties to authors in accordance with the general standard, which is 10%, it can be increased or less depending on how famous the author's denomination is and the superiority of the elbow grease produced. document as contained in clause 1 characteristic 1 of collection character 28 of 2014 in reference to document (UUHC) that